(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: The active levels of natural radioactivity Potassium-40, Uranium-238, and Thorium-232 were examined and evaluated in various soil samples from Al-Hilla city by analyzing the results of these samples and comparing them to internationally accepted levels. Materials and Methods: 30 soil samples were collected from different areas in the city of Hilla at a depth of 10–15 cm and examined using a gamma-ray spectrometer. Results: The radioactivity rate for U-238 was (9.36±0.144) Bqkg-1, while it was (16±0.148) Bqkg-1 for Th-232 and (141.5±0.894) Bqkg-1 for K-40. The study’s findings showed that the average radiation effects, such as Radium equivalent (Raeq), the outdoor external dose (Dout), the indoor external dose (Din), the external hazard index (Hex), the internal hazard index (Hin), the representative level index (Iγ), the annual effective dose equivalent (AEDE), and the lifetime cancer risks (ELCR), are as follows: (43.13) Bqkg-1, (20.16) nGyh-1, (37.67) nGy/h, (0.12), (0.11), (0.32), (0.185) mSvy-1, and (0.69) x10-3, respectively. Conclusions: The examination of the echelons of naturally occurring radioactivity in the areas in the center of Hilla has produced a wealth of data demonstrating that the measured concentrations of natural radionuclides are within acceptable bounds and represent typical levels of radioactivity.